Alternatives of chemical thinning in ‘Fuji Suprema’ apples - Petri, José Luiz (2018)
Abstract – The fruit thinning of an apple tree is one of the most important cultural practices for increasing fruit size and quality, in addition to avoiding the alternation of production. Chemical thinning is widely used in apple growing, because it reduces the need for labor and allows the activity to be performed in an appropriate period. Combinations of ﬂowering and post-ﬂowering chemical thinners have provided more eﬀectve results for cultivars with high fruit set. The aim of this work was to evaluate the response of the application of combinations of ﬂowering and post-ﬂowering chemical thinners in ‘Fuji Suprema’ apple tree. The experiments were conducted from 2011 to 2013 evaluating the combination of benzyladenine (BA) with GA4+7+BA, ANA and ethephon, used in diﬀerent concentrations and times of application. The ﬂowering and post-ﬂowering chemical thinners are efficient for ‘Fuji Suprema’ apple tree. The ﬂowering chemical thinners GA4+7+BA or BA and the post-ﬂowering chemical thinner BA combined with ANA or ethephon presented the closest results to hand thinning, being an efficient alternative.